Phenomenon of Phonemic Dissimilation of Post- Graduate Students/ Department of Arabic and English Language/ College of Education for Women: A comparative experimental study - Abbas, Hind Fadhil; Alsaadi, Shatha Kathim (Al-Adab Journal, 2022)
Phonemic dissimilation is one of the phonetic phenomena in which two similar sounds change into two different sounds because of historical and contextual reasons. Since the role of phonemic dissimilation in the pronunciation of words is critical, the two researchers have done an experimental study on master's students in the Arabic and English departments to determine the extent of their understanding and awareness of this phenomenon. Therefore, (10) words were selected in each of the Arabic and English languages, and after they were presented to jury members, the test was applied to the female students. the percentages are used to calculate the differences in vocal performance. The two researchers reached a number of recommendations and suggestions.